Innamincka Talk: A grammar of the Innamincka dialect of Yandruwandha with notes on other dialects - Breen, Gavan (ANU Press, 2015)
Innamincka Talk: A grammar of the Innamincka dialect of Yandruwandha with notes on other dialects is one of a pair of companion volumes on Yandruwandha, a dialect of the language formerly spoken on the Cooper and Strzelecki Creeks and the country to the north of the Cooper, in the northeast corner of South Australia and a neighbouring strip of Queensland. The other volume is entitledInnamincka Words. Innamincka Talk is the more technical work of the two and is intended for specialists and for interested readers who are willing to put some time and effort into studying the language.Innamincka Words is for readers, especially descendants of the original people of the area, who are interested in the language, but not necessarily interested in its more technical aspects. It is also a necessary resource for users of Innamincka Talk. These volumes document all that could be learnt from the last speakers of the language in the last years of their lives by a linguist who was involved with other languages at the same time. These were people who did not have a full knowledge of the culture of their forebears, but were highly competent, indeed brilliant, in the way they could teach what they knew to the linguist student.